English Proficiency and Job Opportunities in Digital Era: A Bridge or a Barrier? - Yandri Ahmad Rifandi; Aminah Aminah (Universitas Islam Sultan Agung, 2026)
The rapid transformation of the global labor market driven by digitalization, artificial intelligence (AI), and technological innovation has significantly reshaped the competencies required for graduate employability, positioning English proficiency as a strategic asset for workforce competitiveness. Despite the growing body of empirical research, existing evidence remains fragmented across different educational and national contexts, limiting a comprehensive understanding of the role of English proficiency in shaping employment opportunities in the digital era. This study aims to synthesize recent empirical evidence on the relationship between English proficiency and job opportunities through a qualitative literature review. The review adopted the PRISMA 2020 framework to identify, screen, and select relevant peer-reviewed studies published between 2021 and 2025 from Scopus, ERIC, Google Scholar, and the Directory of Open Access Journals (DOAJ). 17 studies were selected and analyzed using thematic analysis to identify recurring patterns and conceptual relationships. The synthesis revealed five overarching themes: (1) English proficiency as employability capital, (2) English proficiency in supporting workplace communication, (3) English proficiency as a catalyst for career advancement, (4) English proficiency in enhancing digital workforce readiness, and (5) English proficiency as a barrier to employment opportunities. The findings demonstrate that English proficiency extends beyond linguistic competence and functions as a strategic component of employability by strengthening graduates' competitiveness, facilitating professional communication, promoting career mobility, and enabling participation in digitally mediated workplaces. Conversely, inadequate English proficiency continues to restrict access to employment, professional development, and international career opportunities. This review contributes to the literature by integrating empirical evidence from developing Asian countries and conceptualizing English proficiency within the frameworks of human capital, digital employability, and sustainable employability. The findings provide practical implications for higher education institutions, curriculum developers, and policymakers in designing employability-oriented English language education that aligns with the evolving demands of the global digital workforce.